The Role of the Workplace in Ethnic Wage Differentials - John Forth; Nikolaos Theodoropoulos; Alex Bryson (Global Labor Organization (GLO), 2021)
Using matched employer-employee data for Britain, we examine ethnic wage differentials among full-time employees. We find substantial ethnic segregation across workplaces: around three-fifths of workplaces in Britain employ no ethnic minority workers. However, this workplace segregation does not contribute to the aggregate wage gap between ethnic minorities and white employees. Instead, most of the ethnic wage gap exists between observationally equivalent co-workers. Lower pay satisfaction and higher levels of skill mismatch among ethnic minority workers are consistent with discrimination in wage-setting on the part of employers. The use of job evaluation schemes within the workplace is shown to be associated with a smaller ethnic wage gap.
Keywords: J16; J31; M52; M54; 330; ethnic wage gap; workplace segregation; skill mismatch; pay satisfaction; job evaluation